Effect of the phase-transition fluid reaction heat on wellbore temperature in self-propping phase-transition fracturing technology. (15th February 2023) - Zhang, Nanlin; Chen, Zhangxin; Luo, Zhifeng; Liu, Pingli; Chen, Weiyu; Liu, Fushen
Abstract: The key to the success of self-propping phase-transition fracturing (SPF) technology using two immiscible fluids to generate proppants in-situ in a reservoir lies in accurate calculations of temperature distribution. As the reaction heat of phase-transition fluid (PF) significantly affects wellbore temperature, reaction kinetic parameters were fitted by experimental data based on the Arrhenius equation, and the transient temperature model considering the reaction heat is established based on the first law of thermodynamics. This model is discretized by the finite difference method and solved by the successive over-relaxation iteration method. The results show that the reaction heat effect on wellbore temperature cannot be ignored. A temperature value and a phase transition time at the well bottom are the largest in the whole wellbore, so the phase transition ratio at the well bottom is the largest. Moreover, since the PF with incomplete phase transition in a wellbore is easier to enter fractures and prop fracture fronts, it is recommended to inject a pre-pad fracturing fluid before injecting PF to reduce wellbore temperature and prevent premature phase transition in the wellbore. These findings can help reveal the action mechanisms of different injection methods and parameters in a heat transfer process, which is of great significance for the theoretical research and field implementation of SPF technology. Highlights: A wellbore temperature model considering reaction heat is established. The reaction kinetic parameters were fitted by DSC experimental data. The action mechanisms of injection parameters on temperature are revealed.